PKM Improving Digital Literacy for Indonesian People in Tsukuba Prefecture, Japan - Darusman; Firmansyah, Ferdi; Maula Rahmawan, Theofan (IJECS: Indonesian Journal of Empowerment and Community Services, 2026)
ABSTRACT The use of social media is still spontaneous, undirected, and has not been supported by an effective content management strategy. The main challenges faced include a lack of understanding of algorithmic platforms, inconsistencies in content creation, as well as a lack of engaging content editing capabilities. The purpose of this Community Service (PKM) activity is to improve digital literacy and social media skills to build personal and business branding for the Indonesian diaspora living in Tsukuba Prefecture, Japan. One of the obstacles faced by the Indonesian community in Japan is the low awareness of the use of social media, which is only used to share personal life stories, and the lack of technical skills to create interesting and engaging digital content. The solution approach implemented was to provide education and direct mentoring on social media utilization strategies and video content creation techniques that leave a positive impression on the audience. The results of this activity showed a 40.2% increase in awareness of the importance of building personal and business branding and a 55.3% increase in video editing skills after the educational activity was implemented. The conclusion of this PKM activity is that education on social media utilization strategies and mentoring in editing digital video content have been proven to provide positive improvements for Indonesian diaspora in Japan. Keywords: Digital Literacy; Social Media ; Personal Branding